2008
DOI: 10.1124/dmd.107.020099
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Cytochromes P450 3A4 and 3A5 to the Metabolism of the Phosphodiesterase Type 5 Inhibitors Sildenafil, Udenafil, and Vardenafil

Abstract: ABSTRACT:The role of the genetically polymorphic CYP3A5 in the metabolism of CYP3A substrates is unclear. We investigated the contributions of the CYP3A4 and CYP3A5 isoforms to the metabolism of the phosphodiesterase type 5 inhibitors (PDE5Is) sildenafil, udenafil, and vardenafil. In vitro incubation studies of sildenafil N-demethylation, udenafil N-dealkylation, and vardenafil N-deethylation were conducted using recombinant CYP3A enzymes and 15 human liver microsome (HLM) preparations with predetermined CYP3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 29 publications
2
44
0
1
Order By: Relevance
“…propranolol to 5-hydroxypropranolol (CYP2D6) [29], tolbutamide to 4-hydroxytolbutamide (CYP2C9) [30], naproxen to O-desmethylnaproxen (CYP1A2) [31], acetanilide to acetaminophen (CYP1A2) [31,32] and sildenafil to N-desmethylsildenafil (CYP3A4) [33].…”
Section: Discussionmentioning
confidence: 99%
“…propranolol to 5-hydroxypropranolol (CYP2D6) [29], tolbutamide to 4-hydroxytolbutamide (CYP2C9) [30], naproxen to O-desmethylnaproxen (CYP1A2) [31], acetanilide to acetaminophen (CYP1A2) [31,32] and sildenafil to N-desmethylsildenafil (CYP3A4) [33].…”
Section: Discussionmentioning
confidence: 99%
“…11) They also demonstrated that the mean rate for N-desalkyl metabolite formation from sildenafil was high in human liver microsome preparations with CYP3A5 activity (heterozygous for CYP3A5*1/*3 alleles) compared to those with null CYP3A5 activity (homozygous for CYP3A5*3 allele). 11) These results suggested that genetic polymorphism of CYP3A5 at least partly contributes to interindividual variability in the disposition of sildenafil. On the other hand, tadalafil is eliminated predominantly by oxidative metabolism to a catechol via demethylenation ( Fig.…”
mentioning
confidence: 83%
“…1). Recently, Ku et al 11) showed that both CYP3A4 and CYP3A5 played a significant role in the metabolism of sildenafil using CYP3A supersomes. That is, the intrinsic clearance for N-dealkylation of sildenafil by CYP3A5 and CYP3A4 were 0.09 and 0.07 µL/ min/pmol P450, respectively.…”
mentioning
confidence: 99%
“…CYP3A4 is responsible for the metabolism of more than 50% of therapeutic drugs 15) such as nifedipine, 16,17) triazolam, 18) simvastatine, [19][20][21] and vardenafil. 22) Because of the pharmacological properties of gastrointestinal drugs, it is often used concomitantly with other therapeutic agents. Therefore, careful attention is needed to avoid drug interactions through CYP3A4 inhibition.…”
Section: Discussionmentioning
confidence: 99%